The Influence of Individual Characteristics on Cultural Consumption from the Perspective of Complex Social Network - Hui Liu; Shuang Lu; Ximeng Wang; Shaobo Long (Complexity)
In the era of the digital economy, social network as an important social capital has an important influence on individual consumption decision-making. This article uses the latest data from the China Household Finance Survey (CHFS) in 2017 to analyze the impact of personal characteristics on cultural consumption behavior under the influence of social networks from a theoretical and empirical perspective. Studies have shown that (1) social networks have a significant impact on cultural consumption; compared to gift money and social interaction, communication costs have a greater impact on cultural consumption; (2) communication costs have a greater impact on education consumption, entertainment consumption, and tourism consumption; (3) under the influence of social networks, individual characteristics have a significant impact on cultural consumption; (4) the higher the level of education, the easier it is for cultural consumption. There are intergenerational differences in cultural consumption expenditures of different age groups. It is easier for people to consume entertainment than the elderly.